2015
DOI: 10.1002/ase.1541
|View full text |Cite
|
Sign up to set email alerts
|

Does emotional intelligence change during medical school gross anatomy course? Correlations with students’ performance and team cohesion

Abstract: Emotional intelligence (EI) has been associated with increased academic achievement, but its impact on medical education is relatively unexplored. This study sought to evaluate change in EI, performance outcomes, and team cohesion within a team-based medical school anatomy course. Forty-two medical students completed a pre-course and post-course Schutte Self-Report Emotional Intelligence Test (SSEIT). Individual EI scores were then compared with composite course performance grade and team cohesion survey resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 52 publications
(53 reference statements)
2
4
0
Order By: Relevance
“…This discovery re ects EI can be increased with deliberate practice and training, unlike Intelligence Quotient [17]. These ndings are consistent with those of Holman et al [6]. The evidence of this study also shows that teachers' in-depth analysis of various emotions in the classroom, good use of various media, and proper guidance of students to experience emotion can promote medical students' emotional management and enhance their understanding of emotions.…”
Section: Emotional Intelligencesupporting
confidence: 90%
See 2 more Smart Citations
“…This discovery re ects EI can be increased with deliberate practice and training, unlike Intelligence Quotient [17]. These ndings are consistent with those of Holman et al [6]. The evidence of this study also shows that teachers' in-depth analysis of various emotions in the classroom, good use of various media, and proper guidance of students to experience emotion can promote medical students' emotional management and enhance their understanding of emotions.…”
Section: Emotional Intelligencesupporting
confidence: 90%
“…(1) why we should learn about emotions, (2) common emotional problems of college students, (3) how to adjust the mood, (4) how to identify negative emotions, (5) how to seek the help of a psychologist, (6) case analysis, and (7) production and display of sitcom. Students were divided into 10 groups and encouraged to complete all modules during every learning session.…”
Section: Educational Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…e importance of emotional intelligence in physicians has fascinated researchers in terms of discovering the association of emotional intelligence with retention, promotion, and efficiency among academic practitioners. A growing number of published studies on emotional intelligence among medical students and resident trainees supports this issue's importance [36][37][38][39]. Our findings suggested that emotional intelligence could be a potential negative predictor of burnout.…”
Section: Discussionsupporting
confidence: 68%
“…The supplemental instruction program provides exposure to the majority of the material presented in the fall MGA course, which aids in retention and recall of this difficult subject matter during the first semester of medical school. The largely near‐peer‐taught course also introduces students to the anatomy laboratory, which is considered a high stress environment with the demands of dissection coupled with student expectations to learn as they go (Holman et al, ; Nwachukwu et al, ). The ABC course utilizes prosected donors so that the students have more time to focus on learning the anatomy rather than spending time dissecting (the fall MGA course has a full dissection laboratory component).…”
Section: Discussionmentioning
confidence: 99%